LATIHAN DASAR KEPEMIMPINAN PELATIHAN LEADERSHIP DAN PUBLIC SPEAKING BAGI PENGURUS OSIS SMA/SMK SURAKARTA - JUNTAK, JUSTIN NIAGA SIMAN; SETYANTI, ELIANA; WAHYUDI, SABDA; KRISTRIYANTO, KRISTRIYANTO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This Community Service aims to strengthen the presence of the OSIS (Student Council) at the high school and vocational school levels in Surakarta, where the OSIS members are teenagers aged 15-18 years who are still in the process of seeking their identity and self-discovery. It is crucial for these teenagers to lead school organizations, and this requires the important skill of public speaking, which is especially needed by OSIS members at high schools and vocational schools, particularly in Christian institutions in the city of Surakarta. This basic leadership training provides new knowledge on how students must be prepared to become leaders for themselves and their peers, equipped with the ability to speak in public. This will enhance students' confidence and communication skills, enabling them to relate to their peers in the OSIS management as well as with other OSIS institutions in a healthy and responsible manner. ABSTRAKPengabdian kepada Masyarakat ini memiliki tujuan untuk menguatkan keberadaan OSIS di tingkat SMA maupun SMK di Surakarta, dimana anggota OSIS ini adalah siswa yang berusia remaja yaitu 15-18 tahun dimana mereka masih mencari jati diri dan identitas mereka. Pentingnya para remaja untuk memimpin organisasi sekolah membutuhkan peran penting kemampuan untuk public speaking, dimana hal ini menjadi kebutuhan para pengurus OSIS SMA dan SMK khususnya di lembaga Yayasan Kristen di kota Surakarta. Pelatihan dasar kepemimpinan siswa ini memberikan pengetahuan baru tentang bagaimana para siswa harus siap menjadi pemimpin bagi dirinya dan teman-temannya yang juga dilengkapi dengan kemampuan untuk berbicara dimuka umum. Hal ini akan meningkatkan percaya diri dan kemampuan berkomunikasi siswa untuk berelasi dengan teman-temannya di kepengurusan OSIS maupun antar lembaga OSIS lainnya secara sehat dan bertanggungjawab.